Role of amino acid residues important for nucleic acid binding in human Translin. (October 2019) - Gupta, Alka; Pillai, Vinayaki S.; Chittela, Rajani Kant
Highlights: Functional role of Y85, R86, H88, R92 and K193 in human translin is established. K193G mutation abolished the octameric state of Translin and its ability to bind nucleic acids. R86 and R92 residues found to be to be important for DNA/RNA binding. H88A mutant showed higher nucleic acid binding affinity in comparison to the wild type Translin. Abstract: Translin is a multifunctional DNA/RNA binding protein involved in DNA repair and RNA metabolism. It has two basic regions and involvement of some residues in these regions in nucleic acid binding is established experimentally. Here we report the functional role of four residues of basic region II, Y85, R86, H88, R92 and one residue of C terminal region, K193 in nucleic acid binding using substitution mutant variants. CD analysis of the mutant proteins showed that secondary structure was maintained in all the mutant proteins in comparison to wild type protein. Octameric state was maintained in all the mutants of basic region as evidenced by TEM, DLS, native PAGE and gel filtration analyses. However, K193G mutation completely abolished the octameric state of Translin protein and consequently its ability to bind ssDNA/ssRNA. The mutants of the basic region II exhibited a differential effect on nucleic acid binding, with R86A and R92G as most deleterious. Interestingly, H88A mutant showed higher nucleic acid binding affinity in comparison to the wild type Translin. An in silico analysis of the mutant variant sequences predicted all the mutations to be destabilizing, causing increase in flexibility and also leading to disruption of local interactions. The differential effect of mutations on DNA/RNA binding where octameric state is maintained could be attributed to these predicted disturbances.